Revision of the genus Manayunkia Leidy, 1859, and establishment of two subfamilies within Fabriciidae (Annelida, Sabellida) - Bick, Andreas; Bastrop, Ralf (Zootaxa, 2025)
Species of Manayunkia Leidy, 1859 are small, semi-sedentary, tube-dwelling polychaetes. Manayunkia species are found worldwide in fresh and brackish water, in marine habitats and even in hypersaline lakes. Eleven species are currently assigned to the genus. In this revision the diagnostic characters of all species are considered and discussed, especially the structure of the radiolar crown, the presence of transitional chaetae and transitional uncini as well as the brood chamber. This study also provides information on the systematics, phylogenetic relationships, biology, ecology and geographical distribution of all species. Some of the characters unique to Manayunkia and closely related genera suggest a unique phylogenetic lineage within the Fabriciidae, which should also be designated by a taxonomic category. Based on these apomorphic characters a new subfamily, the Manayunkiinae subfam. nov., is proposed. This is the sister taxon of Fabriciinae subfam. nov. The separation of Manayunkiinae subfam. nov. and Fabriciinae subfam. nov. is also supported by phylogenetic analyses of 18S rDNA and 28S rDNA sequence data.